Pengembangan Bahan Ajar Kimia SMK Teknologi Kelas X Berbasis Kontekstual - Asliyani Asliyani; Muhammad Rusdi; Asrial Asrial (Universitas Jambi, 2014)
This development research is conducted at SMKN 3 Jambi, the purpose is to develop contextual based chemistry learning material for Xth grade Technological Vocational High School (SMK) with content and contex representative enough for SMKN 3 students. The model used in this research development is the type 1 development mode from Richey by adopting the development model of Dick & Carey. This development research is conducted in four important steps, they are analysis, design, development, and evaluation. The data are collected using openended questionaire. The subjects are students from class X TPM1, X TKR2, and X TKR3. These samples are taken randomly but remain to represent each student ability level, high, medium and very low. The research result shows the positif respond towards the developed product. Based on the collected and analyzed data, it can be concluded that the developed product is interesting, simple and easy to understand, can increase student’s positif characters such as interest, participation, responsibility, and relate to student selected skill.